Local voices and action: concluding discussion. Issue 1 (4th February 2019) - Gibson, Terry David; Aka, Festus Tongwa; Aretaake, Ruiti; Bari, Sarwar; Chantry, Guillaume; Gupta, Manu; Molina, Jesusa Grace; Norton, John; Parajuli, Bhubaneswari; Rahmawati, Hepi; Shresha, Nisha
Abstract : Purpose: The purpose of this paper is to discuss the findings from the body of case studies offered in the issue, combined with three external perspectives on local voices and action. Design/methodology/approach: Using as its basis the eight key case studies and three external contributions to the special issue, the paper offers a theoretical framework as a basis for discussion of this material. Through this, it identifies possible modes of action understood through the theoretical framework and elaborated through the specific cases. It concludes with proposals for further work. Findings: The discussion finds that from a local perspective, the ambitions of local populations and local NGOs to achieve emancipatory change depend on the scope for local collaboration and partnerships to exercise influence on underlying risk factors. It resolves the suggested tension between operating within, and outside the system through the concept of "legitimate subversion". Originality/value: It is felt that the original recording of case studies of local level action combined with the process of iterative critical reflection on the part of the contributors offers a novel approach to knowledge creation from practice, and offers insights bridging theoretical and practitioner perspectives into means of addressing underlying risk factors affecting local populations.